Vaginal delivery of the second twin in unengaged cephalic presentation. (2nd January 2021) - Arabin, Birgit; Kyvernitakis, Ioannis; Hamza, Amr; Maul, Hoilger; Di Tommaso, Mariarosaria; van Eyck, Jim; Nizard, Jacky
Abstract: In accordance with women's preferences guidelines, referring to population-based and randomized trials, which recommends counseling women with vertex-first twins to attempt a vaginal delivery. Yet, the rising rates of twin caesareans are associated with the decline in skills of senior and junior obstetricians. Although noncephalic second twins have been in the focus of interest, prompt delivery of cephalic second twins can be trickier when the head does not engage. We illustrate how to avoid complications during instrumental delivery or internal podalic version and breech extraction of the second twin encouraging to start when membranes are still intact.